PEMBARUAN UBRUG SENTRA AGATA MELALUI KOLABORASI: TELAAH BENTUK ESTETIS THE “UBRUG” RENEWAL OF SENTRA AGATA THROUGH C - Zanuar Eko Rahayu (SENDIKRAF Jurnal Pendidikan Seni dan Industri Kreatif, 2021)
The current study aims at (1) describing any collaborated arts elements in the ubrug renewal carried out by arts extracurricular activities of Sentra Agata in SMAN 2 Pandeglang Banten, and (2) analysing the aesthetic form of "ubrug” renewal using the principles of unity, theme, thematic variations, balance, evolution, and hierarchy. The techniques of analysis include doing ubrug-related library research, interviewing ubrug doers and arts academics, and applying aesthetic form theory to analyze the seen performances. The findings of this study demonstrate that renewals are carried out through “ubrug” collaboration with the arts of puppetry that is present as a source of stories, the narration of “murwa” puppet style in the opening scene, the figure of Semar in the form of “golek” puppets, and the arts of “bedug” in the composition of music for “tatalu” and “lalaguan”, the action of “ngadu bedug”, and “bedug rampak” at the end of the performances. The “ubrug” renewal through collaboration, correspondingly, justifies all principles of aesthetic form characteristic so that the blend of performance could be produced.